HO CHI MINH’S THOUGHTS ON GENDER EQUALITY IN THE POLITICAL SPHERE IN VIETNAM AND STRATEGIC IMPLICATIONS FOR INDONESIA - Nguyen, Tri Minh (JWP (Jurnal Wacana Politik), 2026)
This paper provides an exhaustive examination of the theoretical foundations of Ho Chi Minh’s thought regarding gender equality and its institutionalization within the political fabric of the Socialist Republic of Vietnam. Focusing on the contemporary period (2021–2026), the analysis evaluates the efficacy of the Vietnamese model of State Feminism in achieving descriptive and substantive representation for women in legislative and executive bodies. Furthermore, the paper conducts a rigorous comparative analysis with the Republic of Indonesia, particularly following its 2024 general elections, to identify structural, cultural, and legal divergences. By synthesizing data from government reports, international indices, and academic literature, this study argues that, while Ho Chi Minh’s thought provides a robust ideological license for women’s political inclusion, the transition to a market economy and the persistence of patriarchal norms create a double burden paradox. Conversely, Indonesia’s challenges highlight the fragility of electoral gender quotas in the absence of unified state-driven recruitment pipelines and strong enforcement mechanisms against Violence Against Women in Politics (VAWP). The report concludes with actionable lessons for Indonesia derived from the Vietnamese experience, emphasizing the need to move beyond candidacy quotas toward result-oriented institutional engineering.